The Production of Pestil (Fruit leather) from Different Hawthorn (Crataegus spp.) Fruits - Alper Baran; Hayrunnisa Nadaroğlu (Turkish Journal of Agriculture: Food Science and Technology)
Pestil is one of the important foods traditionally produced in Türkiye, with high energy, vitamin and mineral content. It is obtained by naturally drying the pulp obtained from different kinds of fruits after mixing it with ingredients such as sugar and flour. In regions where the fruiting period depends on the season, fruit pulp is produced in order to benefit from it in winter. In addition, bioactive components originating from the fruit increase the nutritional value. In this study, the physicochemical and antioxidative properties of the pestil obtained from three different Hawthorn fruits (Crataegus meyeri, Crataegus turkestenica and Crataegus orientalis) known to have positive effects on health were investigated. The results revealed that, depending on the fruit type, pestil samples have high antioxidative properties (IC50: 50.11±0.16-52.1±2.14 mg/mL) due to the high phenol content (39.8±0.16-52.95±1.21 mg GA/g DW). In this context, in the present study, it has been seen that the pestil prepared with the traditional method from three different Hawthorn fruits should be industrially produced as a product for people to access healthy and various foods today.